Analisis Strategi Pemasaran Digital Produk Pembiayaan Cicil Emas di Bank Syariah Indonesia Kantor Cabang Pembantu Surabaya Diponogoro - Afifah, Afifah; Mashudi, Mashudi (Alkasb: Journal of Islamic Economics, 2022)
This study aims to determine the marketing strategy of digital product financing for gold installments at Bank Syariah Indonesia sub-branch office Surabaya Diponogoro. The subjects of this study were employees of BSI KCP Surabaya Diponegoro. This study uses a descriptive analysis method using primary and secondary data. Primary data was obtained from the first field source through direct interviews with the BSI KCP Surabaya Diponegoro. And secondary data was obtained from books, journals, research reports, and websites. Based on the results of research on Digital Product Marketing Strategies for Gold Installment Financing at Bank Syariah Indonesia Sub-Branch Office Surabaya Diponegoro uses several strategies, namely STP (segmentation, targeting, positioning), 4P: Product (product), Price (price), Place (place/distribution channel ) and Promotion (promotion) and SWOT (strengths (strengths), weaknesses (weaknesses), opportunities (opportunities), and threats (threats).